A cleaning agent for resisting corrosion of electrical and mechanical equipment of a bullet train and a preparation method thereof

CN118461013BActive Publication Date: 2026-10-09ZHTWY BEIJING TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410349550.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-26
Publication Date
2026-10-09
Estimated Expiration
2044-03-26

AI Technical Summary

Technical Problem

一般的机械设备清洗剂包含有浓碱液,虽然清洁作用明显但是对机械设备具有严重的腐蚀性,而且一般的机械设备清洗剂大多采用泡沫型清洗剂,虽然能够有效的去除油污等杂质,但是泡沫型清洗剂会加大对金属表面的氧化和腐蚀作用,也对设备表面造成了一定的损害

Benefits of technology

[0032] In this invention, molybdenum disulfide is ultrasonically treated using a liquid-phase exfoliation method to obtain molybdenum disulfide nanosheets. These nanosheets are then uniformly embedded into a polyvinyl butyral matrix to obtain an anti-corrosion material. This anti-corrosion material can form a coating on the metal surface, acting as a barrier to prevent corrosive media from eroding the substrate. Furthermore, the good bonding between the two materials continuously enhances the labyrinth effect of the coating, reducing surface defects and lowering the permeability of corrosive media, thus providing excellent anti-corrosion performance. Simultaneously, because the molybdenum disulfide nanosheets have a layered structure, they can form a continuous phase layered structure through intercalation and stacking, further strengthening the barrier effect and slowing down the erosion rate of corrosive media on the substrate, thereby enhancing the anti-corrosion effect. To further improve the anti-corrosion effect and allow the substrate material to be used better in harsh environments, this invention uses cobalt nitrate and sodium sulfide as the cobalt and sulfur sources, respectively, employing a two-step hydrothermal method. The cobalt sulfide nanosheets are obtained through a hydrothermal reaction in a high-pressure reactor, and then used as... Using cobalt nitrate, hexadecyltrimethylammonium bromide, and urea as a deposition carrier, a large number of micro- and nanorod-structured cobalt tetroxide are deposited on cobalt sulfide nanosheets using a combination of hydrothermal and calcination methods, thus obtaining a composite nanomaterial. This composite nanomaterial is also introduced into a polyvinyl butyral matrix and compounded with hydrocarbons, nonionic surfactants, bentonite, sodium carboxymethyl cellulose, magnesium aluminum silicate, dispersants, complexing agents, solubilizers, and water to obtain an anti-corrosion cleaning agent. When this anti-corrosion cleaning agent is used, due to the large number of micro- and nanorods deposited on the composite nanomaterial during external wiping, these micro- and nanorods act as rolling rods. On the one hand, this reduces the contact area between the composite nanomaterial and the molybdenum disulfide nanosheets, and on the other hand, it creates rolling friction between the two, replacing sliding friction. This makes the movement between the two smoother, allowing for better relative movement between the composite nanomaterial and the molybdenum disulfide nanosheets, thus embedding them together to form a dense structure. This achieves a more complete barrier against external corrosive media and a strong anti-corrosion effect.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of cleaning agent, in particular to a kind of bullet train electrical machinery equipment anticorrosion cleaning agent and preparation method thereof, comprising the following components by weight: hydrocarbons 15-25 parts, non-ionic surfactant 12-16 parts, bentonite 5-8 parts, sodium carboxymethyl cellulose 5-8 parts, magnesium aluminum silicate 3-6 parts, anticorrosion material 4-6 parts, dispersant 1-3 parts, complexing agent 2-6 parts, solubilizer 1-3 parts, water 40-50 parts.The anticorrosion cleaning agent in the present application can form a coating on the metal surface when wiping and cleaning the surface of mechanical equipment, which plays an isolation role and blocks the corrosion of corrosive medium to the matrix.Moreover, the composite nanomaterial and molybdenum disulfide nanosheet contained in the anticorrosion material will move relatively, thereby embedding and inserting together to form a dense continuous phase lamellar structure, thereby achieving a more complete blocking effect on external corrosive medium and achieving a strong anticorrosion effect, so that the mechanical equipment can be better used in harsh environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cleaning agent technology, specifically to an anti-corrosion cleaning agent for high-speed train electrical machinery and equipment and its preparation method. Background Technology

[0002] Cleaning mechanical equipment is an indispensable process in the processing, assembly, storage, and maintenance of such equipment. After a period of normal operation, equipment may become contaminated by suspended solids or sparingly soluble salts present in the feed water. The most common of these contaminants are calcium carbonate precipitate, calcium sulfate precipitate, metal oxide precipitate, silicon deposits, mixtures of inorganic or organic deposits, and synthetic organic matter. Due to the large volume of mechanical equipment used, the workload and amount of cleaning agents required will inevitably increase accordingly. Common mechanical equipment cleaning agents contain concentrated alkaline solutions, which, while effective in cleaning, are highly corrosive to the equipment. Furthermore, most common mechanical equipment cleaning agents are foam-based, which, while effectively removing oil and other impurities, exacerbate oxidation and corrosion on metal surfaces, causing damage to the equipment's surface.

[0003] For example, invention patent CN107858214A discloses a degreasing cleaning agent for mechanical equipment and its preparation method, comprising 15-20 parts of anhydrous sodium metasilicate, 10-15 parts of polyepoxysuccinic acid, 8-12 parts of sodium lauryl ether sulfate, 9-13 parts of sodium dodecyl ether sulfate, 13-17 parts of nonionic Gemini surfactant, 7-11 parts of sodium bicarbonate, 6-10 parts of polydimethyldiallylammonium chloride, 5-9 parts of styrax acetic acid, 4-8 parts of hexadecyl pyridine chloride, 3-7 parts of sulfonated lignin, and lemon... The degreasing agent contains 5-8 parts acid, 10-15 parts shell micro powder, and 15-25 parts deionized water. It has excellent cleaning adhesion and oil-dissolving properties, resulting in rapid cleaning and removal of contaminants. It cleans both the inside and outside of equipment, preventing corrosion. However, as the oil is removed from the surface of the equipment, the metal loses its protective oil film and comes into direct contact with the outside environment. This makes the metal more susceptible to corrosion by external corrosive substances, accelerating the corrosion rate and affecting its normal operation. Summary of the Invention

[0004] To address the problems existing in the prior art, the purpose of this invention is to provide an anti-corrosion cleaning agent for high-speed train electrical machinery and equipment and its preparation method.

[0005] To achieve the above objectives, the present invention provides the following technical solution:

[0006] A corrosion-resistant cleaning agent for high-speed train electrical machinery and equipment comprises the following components in parts by weight: 15-25 parts of hydrocarbons, 12-16 parts of nonionic surfactants, 5-8 parts of bentonite, 5-8 parts of sodium carboxymethyl cellulose, 3-6 parts of magnesium aluminum silicate, 4-6 parts of corrosion-resistant materials, 1-3 parts of dispersant, 2-6 parts of complexing agent, 1-3 parts of solubilizer, and 40-50 parts of water.

[0007] As a further preferred embodiment of the present invention, the hydrocarbon is at least one of n-nonane, n-decane, and n-undecane;

[0008] The nonionic surfactant is at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, and nonylphenol polyoxyethylene ether.

[0009] The dispersant is at least one of sodium dodecylbenzenesulfonate and sodium dodecyl sulfonate;

[0010] The complexing agent is at least one of sodium tripolyphosphate and sodium hexametaphosphate;

[0011] The solubilizer is composed of N-ethylpyrrolidone and tetrahydrofurfuryl alcohol in a mass ratio of (1.2-1.8):1.

[0012] As a further preferred embodiment of the present invention, the method for preparing the corrosion-resistant material is as follows:

[0013] 1) Molybdenum disulfide nanoparticles were uniformly dispersed in N-vinylpyrrolidone and stirred for 30-50 min to form a suspension. The suspension was then placed in an ultrasonic cleaner and ultrasonically treated at 23-28℃ for 5-8 h. The dispersion was then centrifuged for 2-3 h, the suspension was collected, and centrifuged for another 1-3 h. After freeze-drying, molybdenum disulfide nanosheets were obtained.

[0014] 2) Molybdenum disulfide nanosheets are uniformly dispersed in methanol and ultrasonically treated for 1-2 hours to form a dispersion. Then, polyvinyl butyral is added to the dispersion and magnetically stirred for 24-30 hours to mix evenly. Then, composite nanomaterials are added and ultrasonically treated for another 20-50 minutes to obtain the anti-corrosion material.

[0015] As a further preferred embodiment of the present invention, the molybdenum disulfide nanoparticles and N-vinylpyrrolidone are used in a ratio of (5-10) g to (120-180) mL.

[0016] The frequency of the ultrasonic treatment is 40-60kHz.

[0017] As a further preferred embodiment of the present invention, the proportions of molybdenum disulfide nanosheets, methanol, polyvinyl butyral, and composite nanomaterials are (1-3)g:(30-60)mL:(0.3-0.6)g:(0.8-1.7)g;

[0018] The power of the ultrasonic treatment is 200-300W.

[0019] As a further preferred embodiment of the present invention, the preparation method of the composite nanomaterial is as follows:

[0020] 1) Dissolve 4.3-5.2g of cobalt nitrate hexahydrate, 4.5-5.8g of urea, and 1.0-1.5g of ammonium fluoride in 3000-4000mL of deionized water, stir thoroughly, and pour into a high-pressure reactor. React for 9-13 hours. After cooling to room temperature, wash and dry repeatedly with deionized water and set aside. Then, dissolve 0.6-0.9g of sodium sulfate in 3000-4000mL of deionized water, stir thoroughly, and pour into a high-pressure reactor. Add the prepared product and continue to react for 5-10 hours. After cooling to room temperature, remove and wash repeatedly with anhydrous ethanol and deionized water, and then dry to obtain cobalt sulfide nanosheets.

[0021] 2) Cobalt nitrate, hexadecyltrimethylammonium bromide and urea are added to distilled water in sequence and magnetically stirred to dissolve them. Then cobalt sulfide nanosheets are added, ultrasonically dispersed and transferred to a reaction vessel. The vessel is then placed in an oven and heated at 160-167℃ for 3-6 hours. After cooling to room temperature, the mixture is repeatedly washed with distilled water, vacuum dried, and then heated in a tube furnace for 3-5 hours to obtain the composite nanomaterial.

[0022] As a further preferred embodiment of the present invention, the high-pressure reactor has a temperature of 120-130°C.

[0023] As a further preferred embodiment of the present invention, the proportions of cobalt nitrate, hexadecyltrimethylammonium bromide, urea, distilled water, and cobalt sulfide nanosheets are (0.7-1.2)g:(0.08-0.13)g:(0.5-0.8)g:(30-50)mL:(2-6)g;

[0024] The vacuum drying temperature is 60-70℃, and the drying time is 5-10 hours.

[0025] The temperature of the tubular furnace heating is 500-530℃.

[0026] A method for preparing an anti-corrosion cleaning agent for electrical and mechanical equipment of high-speed trains, specifically including the following steps:

[0027] Weigh each component according to weight, add hydrocarbons, nonionic surfactants, dispersants, complexing agents, solubilizers and water to the reaction vessel, heat and stir for 2-5 hours, cool down and discharge the material, then add bentonite, sodium carboxymethyl cellulose, magnesium aluminum silicate and anti-corrosion materials, stir thoroughly and evenly to obtain the required anti-corrosion cleaning agent.

[0028] As a further preferred embodiment of the present invention, the reaction temperature of the reactor is 82-86°C;

[0029] The temperature of the discharged material after cooling is 21-26℃;

[0030] The stirring speed is 200-300 r / min, and the stirring time is 1-3 h.

[0031] Compared with the prior art, the beneficial effects of the present invention are:

[0032] In this invention, molybdenum disulfide is ultrasonically treated using a liquid-phase exfoliation method to obtain molybdenum disulfide nanosheets. These nanosheets are then uniformly embedded into a polyvinyl butyral matrix to obtain an anti-corrosion material. This anti-corrosion material can form a coating on the metal surface, acting as a barrier to prevent corrosive media from eroding the substrate. Furthermore, the good bonding between the two materials continuously enhances the labyrinth effect of the coating, reducing surface defects and lowering the permeability of corrosive media, thus providing excellent anti-corrosion performance. Simultaneously, because the molybdenum disulfide nanosheets have a layered structure, they can form a continuous phase layered structure through intercalation and stacking, further strengthening the barrier effect and slowing down the erosion rate of corrosive media on the substrate, thereby enhancing the anti-corrosion effect. To further improve the anti-corrosion effect and allow the substrate material to be used better in harsh environments, this invention uses cobalt nitrate and sodium sulfide as the cobalt and sulfur sources, respectively, employing a two-step hydrothermal method. The cobalt sulfide nanosheets are obtained through a hydrothermal reaction in a high-pressure reactor, and then used as... Using cobalt nitrate, hexadecyltrimethylammonium bromide, and urea as a deposition carrier, a large number of micro- and nanorod-structured cobalt tetroxide are deposited on cobalt sulfide nanosheets using a combination of hydrothermal and calcination methods, thus obtaining a composite nanomaterial. This composite nanomaterial is also introduced into a polyvinyl butyral matrix and compounded with hydrocarbons, nonionic surfactants, bentonite, sodium carboxymethyl cellulose, magnesium aluminum silicate, dispersants, complexing agents, solubilizers, and water to obtain an anti-corrosion cleaning agent. When this anti-corrosion cleaning agent is used, due to the large number of micro- and nanorods deposited on the composite nanomaterial during external wiping, these micro- and nanorods act as rolling rods. On the one hand, this reduces the contact area between the composite nanomaterial and the molybdenum disulfide nanosheets, and on the other hand, it creates rolling friction between the two, replacing sliding friction. This makes the movement between the two smoother, allowing for better relative movement between the composite nanomaterial and the molybdenum disulfide nanosheets, thus embedding them together to form a dense structure. This achieves a more complete barrier against external corrosive media and a strong anti-corrosion effect.

[0033] The anti-corrosion cleaning agent of this invention, when used to wipe and clean the surface of mechanical equipment, forms a coating on the metal surface under external wiping force. This coating acts as an isolation barrier, preventing corrosive media from eroding the substrate. Simultaneously, the good bonding between the two components continuously enhances the labyrinth effect of the coating, reducing surface defects and lowering the permeability of corrosive media, thus providing excellent anti-corrosion effects. Furthermore, the composite nanomaterials and molybdenum disulfide nanosheets exhibit relative movement, intercalating to form a dense, continuous layered structure. This further enhances the barrier against external corrosive media, achieving extremely strong anti-corrosion effects and enabling the mechanical equipment to operate better in harsh environments. Detailed Implementation

[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0035] In this embodiment of the invention, the hydrocarbon is n-nonane; the nonionic surfactant is fatty alcohol polyoxyethylene ether; the dispersant is sodium dodecylbenzenesulfonate; the complexing agent is sodium tripolyphosphate; and the solubilizer is composed of N-ethylpyrrolidone and tetrahydrofurfuryl alcohol in a mass ratio of 1.8:1.

[0036] Example 1

[0037] A corrosion-resistant cleaning agent for electrical and mechanical equipment of high-speed trains comprises the following components by weight: 15 parts hydrocarbon, 12 parts nonionic surfactant, 5 parts bentonite, 5 parts sodium carboxymethyl cellulose, 3 parts magnesium aluminum silicate, 4 parts corrosion-resistant material, 1 part dispersant, 2 parts complexing agent, 1 part solubilizer, and 40 parts water.

[0038] The preparation method of this anti-corrosion cleaning agent specifically includes the following steps:

[0039] Weigh each component according to weight, add hydrocarbon, nonionic surfactant, dispersant, complexing agent, solubilizer and water to the reactor, heat to 82°C, stir and react for 2 hours, cool to 21°C and discharge, then add bentonite, sodium carboxymethyl cellulose, magnesium aluminum silicate and anti-corrosion material, stir thoroughly at 200 r / min for 1 hour to obtain the required anti-corrosion cleaning agent.

[0040] The preparation method of the corrosion-resistant material is as follows:

[0041] 1) 5g of molybdenum disulfide nanoparticles were uniformly dispersed in 120mL of N-vinylpyrrolidone and stirred at 500r / min for 30min to form a suspension. The suspension was then placed in an ultrasonic cleaner and ultrasonically treated at 23℃ and 40kHz for 5h. The dispersion was then centrifuged at 800r / min for 2h, and the supernatant was collected. The suspension was then centrifuged at 10000r / min for 1h and freeze-dried to obtain molybdenum disulfide nanosheets.

[0042] 2) Dissolve 4.3g of cobalt nitrate hexahydrate, 4.5g of urea, and 1.0g of ammonium fluoride in 3000mL of deionized water, stir thoroughly, and pour into a high-pressure reactor. React at 120℃ for 9h. After cooling to room temperature, wash and dry repeatedly with deionized water for later use. Then dissolve 0.6g of sodium sulfate in 3000mL of deionized water, stir thoroughly, and pour into a high-pressure reactor. Add the above-mentioned prepared product and continue to react at 120℃ for 5h. After cooling to room temperature, remove and wash repeatedly with anhydrous ethanol and deionized water, and then dry to obtain cobalt sulfide nanosheets.

[0043] 3) Add 0.7g cobalt nitrate, 0.08g hexadecyltrimethylammonium bromide and 0.5g urea to 30mL of distilled water in sequence and stir magnetically to dissolve them. Then add 2g cobalt sulfide nanosheets, disperse them evenly by ultrasonication, transfer them to a reaction vessel, place them in an oven, heat them at 160℃ for 3h, cool them to room temperature, wash them repeatedly with distilled water, dry them under vacuum at 60℃ for 5h, and then place them in a tube furnace and heat them at 500℃ for 3h to obtain the composite nanomaterial.

[0044] 4) Disperse 1g of molybdenum disulfide nanosheets uniformly in 30mL of methanol and sonicate at 200W for 1h to form a dispersion. Then add 0.3g of polyvinyl butyral to the dispersion and stir magnetically for 24h to mix evenly. Then add 0.8g of composite nanomaterial and continue sonication for 20min to obtain the corrosion-resistant material.

[0045] Example 2

[0046] A corrosion-resistant cleaning agent for electrical and mechanical equipment of high-speed trains comprises the following components by weight: 20 parts of hydrocarbon, 15 parts of nonionic surfactant, 7 parts of bentonite, 7 parts of sodium carboxymethyl cellulose, 5 parts of magnesium aluminum silicate, 5 parts of corrosion-resistant material, 2 parts of dispersant, 4 parts of complexing agent, 2 parts of solubilizer, and 45 parts of water.

[0047] The preparation method of this anti-corrosion cleaning agent specifically includes the following steps:

[0048] Weigh each component according to weight, add hydrocarbon, nonionic surfactant, dispersant, complexing agent, solubilizer and water to the reaction vessel, heat to 85℃, stir and react for 3 hours, cool to 23℃ and discharge, then add bentonite, sodium carboxymethyl cellulose, magnesium aluminum silicate and anti-corrosion material, stir thoroughly at 260 r / min for 2 hours to obtain the required anti-corrosion cleaning agent.

[0049] The preparation method of the corrosion-resistant material is as follows:

[0050] 1) 7g of molybdenum disulfide nanoparticles were uniformly dispersed in 150mL of N-vinylpyrrolidone and stirred at 700r / min for 40min to form a suspension. The suspension was then placed in an ultrasonic cleaner and ultrasonically treated at 25℃ and 50kHz for 7h. The dispersion was then centrifuged at 1000r / min for 2.5h, and the supernatant was collected. The suspension was then centrifuged at 13000r / min for 2h and freeze-dried to obtain molybdenum disulfide nanosheets.

[0051] 2) Dissolve 4.8g of cobalt nitrate hexahydrate, 5.2g of urea, and 1.3g of ammonium fluoride in 3500mL of deionized water, stir thoroughly, and pour into a high-pressure reactor. React at 125℃ for 11h. After cooling to room temperature, wash and dry repeatedly with deionized water for later use. Then dissolve 0.8g of sodium sulfate in 3500mL of deionized water, stir thoroughly, and pour into a high-pressure reactor. Add the above-mentioned prepared product and continue to react at 125℃ for 7h. After cooling to room temperature, remove and wash repeatedly with anhydrous ethanol and deionized water, and then dry to obtain cobalt sulfide nanosheets.

[0052] 3) Add 1.0g cobalt nitrate, 0.12g hexadecyltrimethylammonium bromide and 0.7g urea to 40mL of distilled water in sequence, stir magnetically to dissolve them, then add 5g cobalt sulfide nanosheets, ultrasonically disperse them evenly, transfer them to a reaction vessel, put them in an oven, heat them at 165℃ for 5h, cool them to room temperature, wash them repeatedly with distilled water, vacuum dry them at 65℃ for 7h, and then put them in a tube furnace and heat them at 520℃ for 4h to obtain composite nanomaterials;

[0053] 4) Disperse 2g of molybdenum disulfide nanosheets uniformly in 50mL of methanol and sonicate at 260W for 1.5h to form a dispersion. Then add 0.5g of polyvinyl butyral to the dispersion and stir magnetically for 28h to mix evenly. Then add 1.5g of composite nanomaterial and continue sonication for 40min to obtain the corrosion-resistant material.

[0054] Example 3

[0055] A corrosion-resistant cleaning agent for electrical and mechanical equipment of high-speed trains comprises the following components in parts by weight: 25 parts of hydrocarbons, 16 parts of nonionic surfactants, 8 parts of bentonite, 8 parts of sodium carboxymethyl cellulose, 6 parts of magnesium aluminum silicate, 6 parts of corrosion-resistant materials, 3 parts of dispersant, 6 parts of complexing agent, 3 parts of solubilizer, and 50 parts of water.

[0056] The preparation method of this anti-corrosion cleaning agent specifically includes the following steps:

[0057] Weigh each component according to weight, add hydrocarbon, nonionic surfactant, dispersant, complexing agent, solubilizer and water to the reactor, heat to 86℃, stir and react for 5 hours, cool to 26℃ and discharge, then add bentonite, sodium carboxymethyl cellulose, magnesium aluminum silicate and anti-corrosion material, stir thoroughly at 300 r / min for 3 hours to obtain the required anti-corrosion cleaning agent.

[0058] The preparation method of the corrosion-resistant material is as follows:

[0059] 1) 10g of molybdenum disulfide nanoparticles were uniformly dispersed in 180mL of N-vinylpyrrolidone and stirred at 800r / min for 50min to form a suspension. The suspension was then placed in an ultrasonic cleaner and ultrasonically treated at 28℃ and 60kHz for 8h. The dispersion was then centrifuged at 1200r / min for 3h, and the supernatant was collected. The suspension was then centrifuged at 15000r / min for 3h and freeze-dried to obtain molybdenum disulfide nanosheets.

[0060] 2) Dissolve 5.2g of cobalt nitrate hexahydrate, 5.8g of urea, and 1.5g of ammonium fluoride in 4000mL of deionized water, stir thoroughly, and pour into a high-pressure reactor. React at 130℃ for 13h. After cooling to room temperature, wash and dry repeatedly with deionized water for later use. Then dissolve 0.9g of sodium sulfate in 4000mL of deionized water, stir thoroughly, and pour into a high-pressure reactor. Add the above-mentioned prepared product and continue to react at 128℃ for 10h. After cooling to room temperature, remove and wash repeatedly with anhydrous ethanol and deionized water, and then dry to obtain cobalt sulfide nanosheets.

[0061] 3) Add 1.2g cobalt nitrate, 0.13g hexadecyltrimethylammonium bromide and 0.8g urea to 50mL of distilled water in sequence and stir magnetically to dissolve them. Then add 6g cobalt sulfide nanosheets, disperse them evenly by ultrasonication, transfer them to a reaction vessel, place them in an oven, heat them at 167℃ for 6h, cool them to room temperature, wash them repeatedly with distilled water, dry them under vacuum at 70℃ for 10h, and then place them in a tube furnace and heat them at 530℃ for 5h to obtain the composite nanomaterial.

[0062] 4) Disperse 3g of molybdenum disulfide nanosheets evenly in 60mL of methanol and sonicate at 300W for 2h to form a dispersion. Then add 0.6g of polyvinyl butyral to the dispersion and stir magnetically for 30h to mix evenly. Then add 1.7g of composite nanomaterial and continue sonication for 50min to obtain the corrosion-resistant material.

[0063] Comparative Example 1: This comparative example is basically the same as Example 1, except that it does not contain anti-corrosion materials.

[0064] Comparative Example 2: This comparative example is basically the same as Example 1, except that step 1 is omitted in the preparation of the anti-corrosion material.

[0065] Comparative Example 3: This comparative example is basically the same as Example 1, except that step 2 is omitted in the preparation of the anti-corrosion material.

[0066] Comparative Example 4: This comparative example is basically the same as Example 1, except that step 3 is omitted in the preparation of the anti-corrosion material.

[0067] Comparative Example 5: This comparative example is basically the same as Example 1, except that step 4 is omitted in the preparation of the anti-corrosion material.

[0068] Test experiment:

[0069] Three-electrode system assembly: Cut the steel shell into small pieces, flatten them, and use insulating tape to stick the surface so that only 1×1cm is exposed. 2 The inner surface of the electrode is used as the working electrode, and a platinum electrode and a calomel electrode are used as the counter electrode and reference electrode, respectively. A 3.5 wt% NaCl solution is prepared as the electrolyte, and the three-electrode system is assembled.

[0070] 10g of the cleaning agents provided in Examples 1-3 and Comparative Examples 1-5 were added to 100mL of deionized water, along with 0.2g of sealing agent (A20-189 sealing agent produced by Shaoguan Metovizhi Chemical Co., Ltd.). The mixture was then diluted to 1000mL, heated to 60℃, immersed in a nickel-plated steel shell, stirred for 5 minutes, removed, and dried. The mixture was then assembled into a three-electrode system. An electrochemical workstation (Shanghai Chenhua CHI760E, China) was used to apply a voltage of -1.0V and the electrochemical impedance was measured and recorded. The corrosion resistance was calculated based on the equivalent circuit diagram fitting. The results are shown in Table 1.

[0071] Table 1

[0072] Corrosion resistance Ω 113.65 115.37 114.02 73.16 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Corrosion resistance Ω 85.73 79.61 87.25 96.17

[0073] As shown in Table 1, the cleaning agent of the present invention can significantly improve the corrosion resistance value of the substrate material after cleaning, thus making it more corrosion resistant and corrosion-resistant.

[0074] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A corrosion-resistant cleaning agent for electrical machinery and equipment in high-speed trains, characterized in that, It includes the following components by weight: 15-25 parts hydrocarbons, 12-16 parts nonionic surfactants, 5-8 parts bentonite, 5-8 parts sodium carboxymethyl cellulose, 3-6 parts magnesium aluminum silicate, 4-6 parts anti-corrosion materials, 1-3 parts dispersant, 2-6 parts complexing agent, 1-3 parts solubilizer, and 40-50 parts water. The method for preparing the corrosion-resistant material is as follows: 1) Molybdenum disulfide nanoparticles were uniformly dispersed in N-vinylpyrrolidone and stirred for 30-50 min to form a suspension. The suspension was then placed in an ultrasonic cleaner and ultrasonically treated at 23-28℃ for 5-8 h. The dispersion was then centrifuged for 2-3 h, the suspension was collected, and centrifuged for another 1-3 h. After freeze-drying, molybdenum disulfide nanosheets were obtained. 2) Molybdenum disulfide nanosheets were uniformly dispersed in methanol and ultrasonically treated for 1-2 hours to form a dispersion. Then, polyvinyl butyral was added to the dispersion and magnetically stirred for 24-30 hours to mix evenly. Then, composite nanomaterials were added and ultrasonically treated for 20-50 minutes to obtain the anti-corrosion material. The preparation method of the composite nanomaterial is as follows: 1) Dissolve 4.3-5.2g of cobalt nitrate hexahydrate, 4.5-5.8g of urea, and 1.0-1.5g of ammonium fluoride in 3000-4000mL of deionized water, stir thoroughly, and pour into a high-pressure reactor. React for 9-13 hours. After cooling to room temperature, wash and dry repeatedly with deionized water and set aside. Then, dissolve 0.6-0.9g of sodium sulfate in 3000-4000mL of deionized water, stir thoroughly, and pour into a high-pressure reactor. Add the prepared product and continue to react for 5-10 hours. After cooling to room temperature, remove and wash repeatedly with anhydrous ethanol and deionized water, and then dry to obtain cobalt sulfide nanosheets. 2) Cobalt nitrate, hexadecyltrimethylammonium bromide, and urea are added sequentially to distilled water and magnetically stirred until dissolved. Then, cobalt sulfide nanosheets are added, ultrasonically dispersed, and transferred to a reaction vessel. The vessel is then placed in an oven and heated at 160-167℃ for 3-6 hours. After cooling to room temperature, the mixture is repeatedly washed with distilled water, vacuum dried, and then heated in a tube furnace for 3-5 hours. This process deposits a large number of micro- and nanorod-structured cobalt tetroxide on the cobalt sulfide nanosheets, thus obtaining the composite nanomaterial. The temperature of the high-pressure reactor is 120-130℃, and the ratio of cobalt nitrate, hexadecyltrimethylammonium bromide, urea, distilled water, and cobalt sulfide nanosheets is (0.7-1.2)g: (0.08-0.13)g: (0.5-0.8)g: (30-50)mL: (2-6)g; The vacuum drying temperature is 60-70℃, and the drying time is 5-10 hours. The temperature of the tubular furnace heating is 500-530℃.

2. The anti-corrosion cleaning agent for electrical machinery and equipment of high-speed trains according to claim 1, characterized in that, The hydrocarbon is at least one of n-nonane, n-decane, and n-undecane; The nonionic surfactant is at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, and nonylphenol polyoxyethylene ether. The dispersant is at least one of sodium dodecylbenzenesulfonate and sodium dodecyl sulfonate; The complexing agent is at least one of sodium tripolyphosphate and sodium hexametaphosphate; The solubilizer is composed of N-ethylpyrrolidone and tetrahydrofurfuryl alcohol in a mass ratio of (1.2-1.8):

1.

3. The anti-corrosion cleaning agent for electrical machinery and equipment of high-speed trains according to claim 1, characterized in that, The molybdenum disulfide nanoparticles and N-vinylpyrrolidone were used in a ratio of (5-10) g to (120-180) mL. The frequency of the ultrasonic treatment is 40-60kHz.

4. The anti-corrosion cleaning agent for high-speed train electrical machinery and equipment according to claim 1, characterized in that, The ratio of molybdenum disulfide nanosheets, methanol, polyvinyl butyral, and composite nanomaterials is (1-3) g : (30-60) mL : (0.3-0.6) g : (0.8-1.7) g; The power of the ultrasonic treatment is 200-300W.

5. A method for preparing an anti-corrosion cleaning agent for electrical machinery and equipment of high-speed trains according to any one of claims 1-4, characterized in that, Specifically, the steps include the following: Weigh each component according to weight, add hydrocarbons, nonionic surfactants, dispersants, complexing agents, solubilizers and water to the reaction vessel, heat and stir for 2-5 hours, cool down and discharge the material, then add bentonite, sodium carboxymethyl cellulose, magnesium aluminum silicate and anti-corrosion materials, stir thoroughly and evenly to obtain the required anti-corrosion cleaning agent.

6. The method for preparing an anti-corrosion cleaning agent for electrical machinery and equipment of high-speed trains according to claim 5, characterized in that, The reaction temperature in the reactor is 82-86℃; The temperature of the discharged material after cooling is 21-26℃; The stirring speed is 200-300 r / min, and the stirring time is 1-3 h.

Citation Information

Patent Citations

  • Degreasing cleaning agent for mechanical equipment and preparation method thereof

    CN107858214A

  • Molybdenum disulfide-antimony sulfide composite material and preparation method and application thereof

    CN106925302A

  • High-protection corrosion-resistant hydrocarbon cleaning agent for cleaning semiconductors and preparation method thereof

    CN113583761A